2004
DOI: 10.1111/j.1745-4530.2004.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Validation of Tomato Pulp Continuous Heat Process

Abstract: This research validated the commercial process applied to tomato pulp (pH 4.3 and 8 Brix) packed in Tetra Brik packages. Spores of Bacillus coagulans and Neosartorya fischeri were selected as targets. The heat resistance of both microorganisms, tested independently, was compared. The redesigned thermal processes were carried out in a aseptic processing and tested by indirect inoculation and retrieval with spores immobilized in alginate/tomato balls. The results showed that processes for 30 s at 115C or greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The induced heat resistance phenomenon has also been discussed by Valdramidis et al (2007). Our results are in agreement with other published works (Fairchild et al 1994;Etoa and Adegoke 1995;Wescott et al 1995;Stabel et al 1997;Tamega and Massaguer 2003;Pacheco and Massaguer 2004). It should also be taking into account that n c was the minimal n value estimated by the fastest particle inside the Microthermics unit, while n e considered all the effects on B. fulva ascospores inside the equipment.…”
Section: Determination Of the Heat Resistance Of Byssochlamys Fulva Isupporting
confidence: 90%
“…The induced heat resistance phenomenon has also been discussed by Valdramidis et al (2007). Our results are in agreement with other published works (Fairchild et al 1994;Etoa and Adegoke 1995;Wescott et al 1995;Stabel et al 1997;Tamega and Massaguer 2003;Pacheco and Massaguer 2004). It should also be taking into account that n c was the minimal n value estimated by the fastest particle inside the Microthermics unit, while n e considered all the effects on B. fulva ascospores inside the equipment.…”
Section: Determination Of the Heat Resistance Of Byssochlamys Fulva Isupporting
confidence: 90%
“…The TDT tubes were heated in a circulating thermostatically controlled oil bath (Dist, DI-B0-1000, AE 0.2°C) at temperatures of 95°C, 97°C, 100°C, 103°C and 105°C. The come-up time of 110 s for 95°C and 120 s for temperatures from 97°C to 105°C is similar to those reported by others (Pacheco & Massaguer, 2004) for tomato pulp. Tubes were completely immersed in the oil bath.…”
Section: Heat Resistance Testssupporting
confidence: 89%
“…Strain and preparation of inocula B. coagulans ATCC7050 was pre-cultivated in NB (Himedia, India) at 37 C for 24 h. The microorganism sporulation was performed in Petri dishes containing Nutrient Agar (Biolife, Italy) supplemented with 5 mg/g of manganese sulfate (Vetec, Brazil) (Pacheco & Massaguer, 2004). Then, plates were incubated over 10 days at 37 C; previous studies, carried out in our laboratory, showed that these conditions resulted in the most resistant B. coagulans spores.…”
Section: Methodsmentioning
confidence: 99%